The factors that affecting training effectiveness at CCM Chemical Sdn. Bhd. Shah Alam / Nurul Ashima Awang - Awang, Nurul Ashima (2010)
Training in organizations is a strategic human resource function. Therefore, organization need to ensure their training is effective. The main objective of the research is to determine the most influence factors that affect training effectiveness in the CCM Chemicals Sdn Bhd. The factors are trainee characteristic, trainer characteristic, organization environment, and technology factor. Besides, the researcher also determines the level of training effectiveness based on employees’ perception in CCM Chemicals Sdn Bhd. Next objective is to determine the relationship between the selected independent variables (training program, trainer, trainee, organization, technology) and training effectiveness. Researcher used questionnaire as a main instrumental in data collection method. The researcher was distributed 40 questionnaires to the respondents at CCM Chemicals Sdn Bhd. After data have been collected, it will be analyzed using frequency, percentage, mean and Pearson Correlation. The results showed that the most influence factor is trainer characteristic. From the findings, the researcher also gives some recommendations for the organization and future researcher.